Witchcraft a very short introduction - Gaskill, Malcolm (Oxford ; New York : Oxford University Press, 2010)
Throughout history, to the present day, witchcraft raises questions about the distinction between reality and fantasy, faith and proof. This book explores witchcraft, both as a contemporary phenomenon and a historical subject. It looks at witch-beliefs and accusations around the world, from pre-history to the present.
Fear -- Heresy -- Malice -- Truth -- Justice -- Rage -- Fantasy -- Culture.
Includes bibliographical references (p. 133-137) and index.
Description based on print version record.
Keywords: Witchcraft; Witchcraft -- History; BODY, MIND & SPIRIT / Magick Studies; BODY, MIND & SPIRIT / Witchcraft & Wicca; Electronic books